2002
DOI: 10.1530/eje.0.1470649
|View full text |Cite
|
Sign up to set email alerts
|

Screening for silent myocardial ischaemia in type 2 diabetic patients with additional atherogenic risk factors: applicability and accuracy of the exercise stress test

Abstract: Objective: Coronary artery disease (CAD), a major cause of mortality in patients with type 2 diabetes (T2D), is often diagnosed late because of silent myocardial ischaemia (SMI). Exercise electrocardiogram testing (ECG) stress is the most utilized screening test for SMI. Its applicability and accuracy, which have never been reported in asymptomatic high-risk T2D patients, have been investigated in this study. Design: A cross-sectional study with coronary angiography as the gold standard for detecting CAD was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 30 publications
6
56
0
1
Order By: Relevance
“…Moreover, the exclusion of CAD on the basis of a negative history of MI or angina pectoris, and absence of ischemic changes on electrocardiograms and during exercise stress testing, was disadvantaged by the possibility that some of the patients without MI may have experienced asymptomatic CAD. In a recent study, 18% of asymptomatic DM2 patients with a negative result of exercise stress testing, presented silent CAD with significant (≥70%) angiographically-documented coronary stenosis [17]. In conclusion, the G(-308)A polymorphism of the TNFα gene is not a risk factor for MI with DM2 in Slo venes of Slavic origin.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, the exclusion of CAD on the basis of a negative history of MI or angina pectoris, and absence of ischemic changes on electrocardiograms and during exercise stress testing, was disadvantaged by the possibility that some of the patients without MI may have experienced asymptomatic CAD. In a recent study, 18% of asymptomatic DM2 patients with a negative result of exercise stress testing, presented silent CAD with significant (≥70%) angiographically-documented coronary stenosis [17]. In conclusion, the G(-308)A polymorphism of the TNFα gene is not a risk factor for MI with DM2 in Slo venes of Slavic origin.…”
Section: Discussionmentioning
confidence: 77%
“…We studied Slovene patients of Slavic origin from independent families who had DM2 lasting more than 10 years: 142 with MI (MI group) and 310 DM2 patients with no history of CAD, and no signs of ischemic changes on electrocardiogram and no ischemic changes during sub maximal stress testing [17]. The diagnosis of MI was based on the World Health Organization criteria [18].…”
Section: Methodsmentioning
confidence: 99%
“…Sixteen percent had abnormal stress test whereas 9% had silent coronary artery disease as defined by angiography. In a study (Bacci et al, 2002) which evaluated 206 higher risk asymptomatic type 2 diabetes patients with peripheral arterial disease and at least 2 cardiovascular risk factors, 19% had an abnormal test and the positive predictive accuracy of the exercise ECG was 79%. These studies collectively support the notion that among higher-risk cohorts of asymptomatic patients with type 2 diabetes nearly 1/3 may have unrecognized coronary artery disease and exercise ECG may be useful in identifying these patients.…”
Section: Exercise Stress Testmentioning
confidence: 99%
“…Studies using routine electrocardiographic exercise treadmill testing, 8 ambulatory electrocardiographic monitoring, 9 and myocardial perfusion scans 10 have each shown that the prevalence of silent ischemia varies between 20%-40% in asymptomatic patients with type 2 diabetes. The prevalence of angiographically demonstrable, significant coronary artery disease in patients with silent ischemia demonstrated by these means varied from 79%-95%.…”
Section: The Realitymentioning
confidence: 99%
“…The prevalence of angiographically demonstrable, significant coronary artery disease in patients with silent ischemia demonstrated by these means varied from 79%-95%. [8][9][10] Yet, investigations to diagnose ongoing ischemia in long-standing type 2 diabetes patients who are asymptomatic are not undertaken routinely and in some instances not even authorized by the third-party payer or health maintenance organization.…”
Section: The Realitymentioning
confidence: 99%